The Effect of the ‘Ruang Belajar’ Web Platform on Improving Reading Literacy Skills of Grade 3 Students at SDN 164 Pekanbaru - Nanda, Dzoelqa Wirya; Kurniaman, Otang; Mulyani, Eva Astuti (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
his study aims to determine the effect of implementing the Ruang Belajar web on reading literacy skills. The study was conducted on grade III students of SDN 164 Pekanbaru. This study used a pretest-post-test non-equivalent control group design. The study took place in the eighth semester of the 2024/2025 school year. The study population consisted of grade III students from SDN 164 Pekanbaru who participated in a web-based Ruang Belajar reading literacy skills learning program. The sample in this study consisted of two groups: class III A, the experimental group, and class III C, the control group. The students involved in this study were 60 students, consisting of 30 students from each of Class III A and Class III C. This assessment used a test instrument that was arranged objectively and systematically. This test instrument was administered twice in each group, namely at the beginning of learning and at the end of learning, to assess students' reading literacy skills. The research data were analyzed using descriptive statistics, namely the mean, and parametric inferential statistics, namely the independent sample t-test. Based on the analysis of the research data, the researchers identified several findings regarding the differences in pretest and posttest results between the experimental class and the control class. Before conducting the research, the researcher conducted a pretest to assess reading literacy ability. In the initial test (pretest), an average percentage score of 85.77% was obtained in the control class (III C). The category of student reading literacy was classified as high. In the experimental class, an average percentage score of 87.5% was obtained in the category of student reading literacy, which was also categorized as high in class III A at SDN 164 Pekanbaru. Based on these data, it can be concluded that the results of student reading literacy fall into the high category.